2014
DOI: 10.1021/es405731j
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic Aromatic Hydrocarbons Show Estrogenic Activity upon Metabolization in a Recombinant Transactivation Assay

Abstract: Heterocyclic aromatic hydrocarbons (hetero-PAHs) are increasingly studied at contaminated sites; especially at former industrial facilities where coal tar-oil was handled, e.g., wood treatment plants, high concentrations of hetero-PAHs are frequently detected in groundwater plumes. In previous studies, fractions of groundwater with high estrogenic activity contained hetero-PAHs and their hydroxylated metabolites. To evaluate this preliminary evidence, selected hetero-PAHs were screened for their estrogenic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 64 publications
(88 reference statements)
2
52
1
Order By: Relevance
“…The REP values in the present study were 2‐fold higher than those in other studies except for the REP value of benzo[ a ]pyrene, which was 10‐fold higher. However, results for the heterocyclic compounds quinoline and dibenzothiophene differed significantly, and although the compounds were not potent inducers in the VM7Luc4E2‐TA, REP values could be determined in the ER‐CALUX bioassay . The MCF‐7 and vMCF‐7 cell lines are genetically similar , which may explain the similarity in REP values of the MVLN assay and the VM7luc4E2 TA.…”
Section: Discussionmentioning
confidence: 98%
“…The REP values in the present study were 2‐fold higher than those in other studies except for the REP value of benzo[ a ]pyrene, which was 10‐fold higher. However, results for the heterocyclic compounds quinoline and dibenzothiophene differed significantly, and although the compounds were not potent inducers in the VM7Luc4E2‐TA, REP values could be determined in the ER‐CALUX bioassay . The MCF‐7 and vMCF‐7 cell lines are genetically similar , which may explain the similarity in REP values of the MVLN assay and the VM7luc4E2 TA.…”
Section: Discussionmentioning
confidence: 98%
“…Heterocylic-PAHs (Hetero-PAHs) are a group of PAH derivatives where one of the carbons within the ring system is replaced by nitrogen, oxygen, or sulfur. Recent research has indicated that some Hetero-PAHs show estrogenic activity 16 and ecotoxicity. 17 Nitro-PAHs (NPAHs) and oxygenated-PAHs (OPAHs) have been detected in the environment 1820 and some are classified as known mutagens and/or possible or probable human carcinogens (group A2 or B2, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…1216 Heterocyclic PAHs, HPAHs (PAH derivatives containing heteroatoms oxygen, nitrogen, or sulphur), have been shown to contribute significantly to toxicity at contaminated sites, and their metabolites have been linked to endocrine disruption. 17,18 …”
Section: Introductionmentioning
confidence: 99%